APLIKASI KOMBINASI PUPUK ORGANIK UNTUK MENINGKATKAN PERTUMBUHAN TANAMAN KANGKUNG DI TANAH MARGINAL - Mani Yusuf; Anwar; Wa Ode Asryanti Wida Malesi; Maya Sari Rupang; Rachmawati Hasid; Abdul Rizal (Politeknik Pertanian Negeri Samarinda, 2022)
The growth of kale is strongly influenced by environmental conditions, one of which is the level of soil fertility. Soil with less fertile conditions can cause plants to grow not optimally. This study aims to determine the effect of a combination of organic fertilizers on the growth of kale on marginal soils. This study used a randomized block design with a combination dose of organic fertilizer consisting of 5 levels of treatment, namely control (P0), 5 tons ha-1 (P1), 10 tons ha-1 (P2), 15 tons ha-1 (P3). ), and 20 tons ha-1 (P4). The variables observed were plant height, number of leaves, leaf area, number of branches and fresh weight. Observational data were analyzed for variance, which showed a significant effect followed by Duncan's Multiple Range Test (DMRT). The results showed that the combination treatment of organic fertilizer had a significant effect on the growth of kale. The best combination treatment of organic fertilizer was obtained by treatment of cow dung + chicken at a dose of 20 tons ha-1 (P4) with an increase in fresh weight of kale by 87.49% compared to the control